Perception of people's business credit and own capital in increasing the productivity of MSME actors in Ciomas District, Serang Regency - Adawiyah, Robiatul; Vinata Putri, Nurmala; Adiyanti, Asrini; Haryadi, Didit; Wahyudi, Wahyudi (International Journal of Applied Finance and Business Studies, 2024)
Micro, small, and medium enterprises (MSMEs) in Indonesia are very important for economic growth and in efforts to overcome unemployment, poverty, and income equality. One of the problems for MSMEs in doing business is Capital Capital. This study aims to develop a model to examine the three variables the author has analyzed to determine the factors that can increase the productivity of MSME actors. This study used the associative descriptive quantitative method with a population of 90 respondents drawn into samples using non-probability sampling saturated sampling / total sampling. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis of people's business credit affects the productivity of MSME actors. Thus, the second hypothesis states that productivity influences the productivity of MSMEs. MSMEsproductivity of MSME actors is influenced by people's business credit and own CapitalCapital, which can simultaneously increase the productivity of MSME competitors rated to make theoretical contributions to the literature in this context, certainly in the context of t.